Market Access and Regional Disparities: New Economic Geography in Europe - Annekatrin Niebuhr (Hamburg Institute of International Economics (HWWA), 2004)
New Economic Geography (NEG) has reached a theoretical consolidation while related empirical tests are still scarce. The present paper aims at providing some evidence on the validity of forces emphasised by NEG. The analysis starts from the nominal wage equation derived from the Krugman ?core-periphery model? and focuses on one of the main propositions of NEG that access advantages raise factor prices. The paper investigates the significance of market access for regional wages and the geographic extent of demand linkages for a cross section of European regions, also taking into account the effects of national borders. The regression analysis covers the period between 1985 and 2000. The results are consistent with the implication of NEG that demand linkages affect the geographic distribution of economic activities, confirming the basic findings of previous analyses. However, regarding the spatial extent of demand linkages, our results differ significantly from previous findings that point to highly localised effects.
Keywords: R12; F12; C21; 330; New economic geography; market access; Europe; Markteintritt; Regionale Lohnstruktur; Regionale Disparität; Neue ökonomische Geographie; Kern-Peripherie-Beziehung; Schätzung; EU-Staaten